Resin composition, interlayer film for laminated glass, and laminated glass
By controlling the glass transition temperature and surface free energy in a polyvinyl acetal resin, and combining the modification of specific functional groups, a resin composition containing no or small amounts of plasticizer is prepared, which solves the plasticization in the prior art The light transmittance and insufficient adhesiveness caused by the agent have achieved high adhesion and corrosion prevention effects.
Patent Information
- Application Number
- CN202180029227.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-21
- Filing Date
- 2021-04-20
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-04-20
AI Technical Summary
The plasticizer in the polyvinyl acetal-based resin used in the existing laminated glass causes the light transmittance of the plexiglass to decrease, and fails to improve adhesion while preventing etching.
By controlling the glass transition temperature to 50°C or less in a polyvinyl acetal resin, the Kaelble-Uy method is used to adjust the value of the polar component of the surface free energy at 0.1 mJ/m2 or more and 8.0 mJ/m2 or less, combined with The modified amount and structure of the specific functional groups are prepared by preparing resin compositions containing no or small amounts of plasticizers.
While preventing etching of resin materials such as polycarbonate, the adhesiveness is significantly improved and the transparency and mechanical properties of the material are maintained.
Smart Images

Figure BDA0003895017330000031 
Figure BDA0003895017330000081 
Figure BDA0003895017330000121
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, an interlayer film for laminated glass comprising the resin composition, and laminated glass. Background Art
[0002] Polyvinyl acetal resins are widely used in laminated glass interlayer films. Laminated glass includes two glass plates and an interlayer film for laminated glass disposed between the two glass plates, and the two glass plates are integrated by the interlayer film for laminated glass. Even if laminated glass is broken by external impact, the amount of glass fragments scattered is small, and it is highly safe, so it is widely used in automobiles, railway vehicles, aircraft, ships, buildings, etc.
[0003] In order to improve the adhesion to the glass plate, the interlayer film for laminated glass using polyvinyl acetal resin, for example, is disclosed in Patent Document 1, which includes a first layer containing a thermoplastic resin such as polyvinyl acetal resin, a plasticizer, and a metal element, and the d component (dispersion component) of the surface free energy in the first layer is made less than 35.9 mJ / m 2 .
[0004] In addition to being used in interlayer films for laminated glass, polyvinyl acetal resins are also being studied for use in various fields such as inks, coatings, enamels for baking, cleaning primers, lacquers, dispersants, adhesives, ceramic green sheets, heat-developable photosensitive materials, and binders for water-based ink receiving layers. Furthermore, attempts have been made to modify polyvinyl acetal resins in order to impart various functions.
[0005] For example, Patent Document 2 discloses an alkyl-modified vinyl acetal polymer that ensures sufficient plasticity, solubility in alcoholic solvents, low viscosity and stability of the solution, is not easily phase-separated from other components, and can obtain a slurry with excellent particle dispersibility and thixotropy, a sheet with excellent strength and flexibility, etc. It is shown that the modified vinyl acetal polymer described in Patent Document 2 is obtained by acetalizing a modified vinyl alcohol polymer containing a monomer unit having -CCONRH (R is an alkyl group having 8 to 29 carbon atoms) in a side chain, having a viscosity-average polymerization degree of 150 to 5000 and a saponification degree of 20 to 99.99 mol%, and having a modification amount of 0.05 to 5 mol% caused by the above-mentioned monomer.
[0006] Furthermore, Patent Document 3 discloses a resin composition for a laminated glass interlayer film comprising a modified polyvinyl acetal resin having an alkoxysilyl group introduced into a side chain via isocyanate, and a plasticizer in order to improve moisture resistance, heat resistance, and penetration resistance.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2017-66007
[0010] Patent Document 2: International Publication No. 2012 / 133351
[0011] Patent Document 3: Japanese Patent Application Publication No. 2003-183059 Summary of the invention
[0012] Problems to be solved by the invention
[0013] Generally, inorganic glass is widely used as a glass plate in laminated glass, but inorganic glass has problems such as being heavy and cracking when impacted. Therefore, the use of organic glass such as polycarbonate plate in laminated glass plates has been studied.
[0014] However, there are cases where the adhesiveness to organic glass such as a polycarbonate plate is not improved even when a conventional interlayer film for laminated glass containing a polyvinyl acetal-based resin is used.
[0015] In addition, the interlayer film for laminated glass containing polyvinyl acetal resin often contains a plasticizer in order to ensure flexibility and improve adhesion to glass. However, if the interlayer film for laminated glass contains a plasticizer, the plasticizer will corrode the resin material such as organic glass during use, thereby reducing the light transmittance of the glass plate composed of organic glass.
[0016] Patent Documents 2 and 3 above show that various functions can be imparted to polyvinyl acetal by modification, but they do not show that the adhesion can be improved while preventing corrosion of resin materials such as polycarbonate.
[0017] Therefore, an object of the present invention is to provide a resin composition comprising a polyvinyl acetal-based resin and capable of preventing corrosion of a resin material such as polycarbonate and improving adhesion to the resin material.
[0018] Means for solving problems
[0019] The present inventors have conducted intensive research and found that the above-mentioned problems can be solved by setting the glass transition temperature of a resin composition containing a polyvinyl acetal resin to below a prescribed value and setting the polar component γsp of the surface free energy obtained by the Kaelble-Uy method to within a prescribed range, thereby completing the following present invention.
[0020] That is, the present invention provides the following [1] to
[23] .
[0021] [1] A resin composition comprising a polyvinyl acetal resin, wherein the glass transition temperature is 50° C. or lower and the polar component γsp of the surface free energy obtained by the Kaelble-Uy method is 0.1 mJ / m 2 Above and 8.0mJ / m 2 The following values.
[0022] [2] According to the resin composition described in [1] above, the polyvinyl acetal resin has at least one functional group selected from the following formula (1-1), formula (1-2), formula (1-3), and formula (1-4).
[0023]
[0024] (In formula (1-1) and (1-2), R 1 , R 2 Each independently represents a hydrocarbon having 2 to 30 carbon atoms. In formulas (1-3) and (1-4), A 1 O.A 2 O is independently an oxyalkylene group having 2 to 4 carbon atoms, and m and n are average repeating numbers of 4 to 200. 3 , R 4 Each is independently an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. It should be noted that in formula (1-3) and formula (1-4), the oxyalkylene group may be a single type or a mixture of two or more types.
[0025] [3] The resin composition according to [2] above, wherein the polyvinyl acetal resin has at least one functional group selected from the group consisting of the functional groups represented by the formula (1-1) and the formula (1-2).
[0026] [4] The resin composition according to [2] or [3] above, wherein the modification amount of the polyvinyl acetal resin caused by the functional groups represented by formula (1-1) and formula (1-2) is 5 mol% or more and 25 mol% or less.
[0027] [5] The resin composition according to [2] above, wherein the polyvinyl acetal resin has at least one functional group selected from the group consisting of the functional groups represented by the formula (1-3) and the formula (1-4).
[0028] [6] The resin composition according to [2] or [5], wherein the modification amount of the polyvinyl acetal resin caused by the functional groups represented by the above formula (1-3) and formula (1-4) is 0.2 mol% or more and 12 mol% or less.
[0029] [7] The resin composition according to any one of [2] to [6] above, wherein the modification amount of the polyvinyl acetal resin caused by the functional groups represented by the above formulas (1-1) to (1-4) is 0.2 mol% or more and 25 mol% or less.
[0030] [8] The resin composition according to any one of [1] to [7] above, which contains no plasticizer or contains 10 parts by mass or less of a plasticizer based on 100 parts by mass of the resin contained in the resin composition.
[0031] [9] The resin composition according to any one of [1] to [8] above, wherein the glass transition temperature is 5° C. or higher.
[0032]
[10] The resin composition according to any one of [1] to [9] above, wherein the polyvinyl acetal resin is a polyvinyl butyral resin.
[0033]
[11] The resin composition according to any one of [1] to
[10] above, wherein the degree of acetalization of the polyvinyl acetal resin is 40 mol% or more and 85 mol% or less.
[0034]
[12] The resin composition according to any one of [1] to
[11] above, wherein the polyvinyl acetal resin has a hydroxyl group content of 0 mol% to 35 mol%.
[0035]
[13] The resin composition according to any one of [1] to
[12] above, wherein the degree of acetylation of the polyvinyl acetal resin is 0.01 mol% to 50 mol%.
[0036]
[14] The resin composition according to any one of [1] to
[13] above, wherein the average degree of polymerization of the polyvinyl acetal resin is 300 or more and 5000 or less.
[0037]
[15] The resin composition according to any one of [1] and [8] to
[14] above, wherein the polyvinyl acetal resin is an unmodified polyvinyl acetal resin and has a hydroxyl group content of 15 mol% or less.
[0038]
[16] An interlayer film for laminated glass, comprising a first layer made of the resin composition according to any one of [1] to
[15] above.
[0039]
[17] The interlayer film for laminated glass according to
[16] above, wherein the interlayer film for laminated glass is composed of the first layer.
[0040]
[18] The interlayer film for laminated glass according to
[16] or
[17] above, wherein the thickness of the interlayer film for laminated glass is 100 μm or more and 2000 μm or less.
[0041]
[19] The interlayer film for laminated glass according to any one of
[16] to
[18] , wherein the first layer constitutes the outermost surface of the interlayer film for laminated glass.
[0042]
[20] A laminated glass comprising the interlayer film for laminated glass according to any one of
[16] to
[19] above, and a first laminated glass component and a second laminated glass component, wherein the interlayer film for laminated glass is arranged between the first laminated glass component and the second laminated glass component.
[0043]
[21] The laminated glass according to
[20] above, wherein at least one of the first laminated glass member and the second laminated glass member is organic glass or an organic film.
[0044]
[22] The laminated glass according to
[21] above, wherein the first layer constitutes the outermost surface of the interlayer film for laminated glass, and the outermost surface constituted by the first layer is in contact with the organic glass.
[0045]
[23] The laminated glass according to any one of
[20] to
[22] above, wherein at least one of the first laminated glass member and the second laminated glass member is a polycarbonate plate or a methacrylate plate.
[0046] Effects of the Invention
[0047] The present invention provides a resin composition comprising a polyvinyl acetal resin and capable of improving adhesion while preventing corrosion of a resin material such as polycarbonate. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is a cross-sectional view schematically showing an interlayer film for laminated glass according to one embodiment of the present invention and a laminated glass including the interlayer film for laminated glass.
[0049] Figure 2 It is a cross-sectional view schematically showing an interlayer film for laminated glass according to one embodiment of the present invention and a laminated glass including the interlayer film for laminated glass.
[0050] Figure 3 It is a cross-sectional view schematically showing an interlayer film for laminated glass according to one embodiment of the present invention and a laminated glass including the interlayer film for laminated glass.
[0051] Figure 4 It is a perspective view for explaining the cross peel test. DETAILED DESCRIPTION
[0052] <Resin composition>
[0053] The resin composition of the present invention comprises a polyvinyl acetal resin, has a glass transition temperature of 50° C. or less, and has a polar component γsp of surface free energy obtained by the Kaelble-Uy method of 0.1 mJ / m 2 Above and 8.0mJ / m 2 The following values.
[0054] In the present invention, since the resin composition has the above-mentioned structure, it is possible to prevent corrosion of resin materials such as polycarbonate and improve adhesion.
[0055] Hereinafter, the resin composition according to one embodiment of the present invention will be described in detail.
[0056] [Glass transition temperature]
[0057] The glass transition temperature (Tg) of the resin composition of the present invention is 50°C or less. If the glass transition temperature (Tg) of the resin composition exceeds 50°C, sufficient flexibility is not exhibited, and it is difficult to achieve good adhesion to resin materials such as polycarbonate and inorganic glass. From the viewpoint of improving flexibility and improving adhesion, the glass transition temperature (Tg) of the resin composition is preferably 48°C or less, and more preferably 45°C or less.
[0058] The lower limit of the glass transition temperature (Tg) of the resin composition is not particularly limited, but is, for example, 5° C. or higher, preferably 10° C. or higher, and more preferably 20° C. or higher from the viewpoint of improving workability without causing tackiness or the like.
[0059] It should be noted that the glass transition temperature of the resin composition can be detected by forming the resin composition into a film, performing viscoelasticity measurement using a dynamic viscoelasticity measuring device, and reading the peak temperature of the loss tangent tanδ obtained from the viscoelasticity measurement result. The details of the measurement conditions are described in the Examples.
[0060] [Surface free energy]
[0061] The polar component γsp of the surface free energy of the resin composition of the present invention obtained by the Kaelble-Uy method is 0.1 mJ / m 2 Above and 8.0mJ / m 2 If the polar component γsp exceeds 8.0mJ / m 2, the polar component γsp of the surface free energy becomes too high, and sometimes the adhesion to hydrophobic resin materials such as polycarbonate is reduced. In addition, sometimes resin materials such as polycarbonate are corroded after long-term use, causing the light transmittance of the resin material to decrease. On the other hand, if the polar component γsp is less than 0.1mJ / m 2 , the polar component of the surface free energy becomes too low, and it is difficult to exhibit high adhesion to hydrophobic resin materials such as polycarbonate.
[0062] From the viewpoint of reducing the corrosion resistance to the resin material and improving the adhesiveness, the polar component γsp of the surface free energy is preferably 6.0 mJ / m 2 Below, more preferably 5.0 mJ / m 2 Below, more preferably 4.5 mJ / m 2 the following.
[0063] In addition, from the viewpoint of improving adhesiveness, the polar component γsp of the surface free energy is preferably 0.3 mJ / m 2 More preferably, 2.0 mJ / m 2 More preferably, 3.0 mJ / m 2 above.
[0064] The polar component γsp of the surface free energy can be calculated by measuring the contact angles of the resin composition with water and diiodomethane at a temperature of 23°C and a relative humidity of 50%, using the following formula. The resin composition is molded into a film, for example, and droplets are formed on the resin composition molded into the film, and the contact angle is measured.
[0065] γs=γsd+γsp
[0066] 72.8(1+cosθH)=2(21.8γsd) 1 / 2 +2(51.0γsp) 1 / 2
[0067] 50.8(1+cosθI)=2(48.5γsd) 1 / 2 +2(2.3γsp) 1 / 2
[0068] γs: surface free energy
[0069] γsd: dispersive component of surface free energy
[0070] γsp: polar component of surface free energy
[0071] θH: contact angle with water
[0072] θI: contact angle to diiodomethane
[0073] [Polyvinyl acetal resin]
[0074] As described above, the resin composition contains a polyvinyl acetal resin. The polyvinyl acetal resin may be a modified polyvinyl acetal resin or an unmodified polyvinyl acetal resin. The modified polyvinyl acetal resin, as described later, has a structure other than an acetal group, a hydroxyl group, and an acetyl group in a side chain.
[0075] The polyvinyl acetal resin is obtained by acetalizing polyvinyl alcohol with an aldehyde and then, if necessary, reacting the polyvinyl alcohol with a modifier or performing a reacetylation treatment. In order to obtain a modified polyvinyl acetal resin, a modified polyvinyl alcohol may be used as the polyvinyl alcohol used as a raw material.
[0076] The structures other than the acetal group, hydroxyl group and acetyl group preferably have a hydrocarbon group having 2 to 30 carbon atoms, and the hydrocarbon group having 2 to 30 carbon atoms is preferably connected to the main chain via a connecting group such as an ester bond or a urethane bond.
[0077] In addition, structures other than acetal group, hydroxyl group and acetyl group may also be polyoxyalkylene groups. The polyoxyalkylene groups preferably have a structure connected to the main chain via any of an ether bond and -CH2O-. It should be noted that the carbon atom of -CH2O- is preferably connected to the main chain.
[0078] That is, the structure other than the acetal group, the hydroxyl group, and the acetyl group is preferably connected to the main chain via any of an ester bond, an ether bond, -CH2O-, and a urethane bond.
[0079] More specifically, the polyvinyl acetal resin preferably has at least one of the functional groups selected from the following formula (1-1) to (1-4), and more preferably has at least one of the functional groups selected from the following formula (1-1) and (1-2). Since the polyvinyl acetal resin has at least the functional groups shown in formula (1-1) to (1-4), the value of the polar component γsp of the surface free energy becomes low and is easily adjusted within the above-specified range. In addition, even if a large amount of plasticizer is not contained, the glass transition temperature (Tg) of the resin composition can be easily reduced.
[0080]
[0081] (In formula (1-1) and (1-2), R 1 , R 2 Each is independently a hydrocarbon group having 2 to 30 carbon atoms. In formula (1-3) and (1-4), A 1 O.A 2O is independently an oxyalkylene group having 2 to 4 carbon atoms, and m and n are average repeating numbers of 4 to 200. 3 , R 4 Each is independently an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. It should be noted that in formula (1-3) and formula (1-4), the oxyalkylene group may be a single type or a mixture of two or more types.
[0082] R 1 , R 2 The hydrocarbon group in may or may not have an aromatic ring, but is preferably an aliphatic hydrocarbon group without an aromatic ring. By using an aliphatic hydrocarbon group, it is easy to make the value of the polar component γsp of the surface free energy low, and it is easy to improve the adhesion with resin materials such as polycarbonate. In addition, the aliphatic hydrocarbon group may be linear, branched, or ring-shaped. For example, if the aliphatic hydrocarbon group is branched, it is easy to make the glass transition temperature (Tg) low.
[0083] Furthermore, the aliphatic hydrocarbon group may or may not have an unsaturated bond. The aliphatic hydrocarbon group is preferably an alkenyl group, an alkyl group, or an alkynyl group, and more preferably an alkyl group.
[0084] R 1 , R 2 The number of carbon atoms in each is preferably 3 or more, more preferably 5 or more, further preferably 7 or more, and further preferably 11 or more. 1 , R 2 The large number of carbon atoms in each of them makes it easy to lower the value of the polar component γsp, and to improve the adhesion to highly hydrophobic resin materials such as polycarbonate. In addition, it is also easy to lower the glass transition temperature (Tg) of the resin composition.
[0085] From the viewpoint of preventing crystallization and improving adhesion, R 1 , R 2 The number of carbon atoms in each is preferably 24 or less, more preferably 20 or less, and further preferably 18 or less.
[0086] Therefore, R 1 , R 2 Each is preferably an alkyl group having 3 to 24 carbon atoms, more preferably an alkyl group having 5 to 20 carbon atoms, further preferably an alkyl group having 7 to 18 carbon atoms, and further preferably an alkyl group having 11 to 18 carbon atoms.
[0087] As R 1 , R 2Specific examples include branched-chain butyl groups such as n-propyl, isopropyl, n-butyl, sec-butyl, and tert-butyl, branched-chain heptyl groups such as n-pentyl, branched-chain pentyl groups, n-hexyl, branched-chain hexyl groups, n-heptyl, isoheptyl, and branched-chain heptyl groups such as 3-heptyl, branched-chain octyl groups such as n-octyl, isooctyl, and 2-ethylhexyl, branched-chain nonyl groups such as n-nonyl and isononyl, n-decyl, branched-chain decyl groups, n-undecyl, branched-chain undecyl groups, n-dodecyl, branched-chain dodecyl groups, n-tridecyl, branched-chain tridecyl groups, n-decyl, branched-chain tridecyl groups, and n-decyl. Tetraalkyl, branched tetradecyl, n-pentadecyl, branched pentadecyl, n-hexadecyl, branched hexadecyl, n-heptadecyl, branched heptadecyl, n-octadecyl, branched octadecyl, n-nonadecyl, branched nonadecyl, n-eicosyl, branched eicosyl, n-heneicosyl, branched heneicosyl, n-docosyl, branched docosyl, n-tricosyl, branched docosyl, n-tetracosyl, branched tetracosyl, oleyl, and the like.
[0088] In formula (1-3) and (1-4), A 1 O.A 2 O is independently an oxyalkylene group having 2 to 4 carbon atoms. The oxyalkylene group having 2 to 4 carbon atoms is oxyethylene, oxypropylene, or oxybutylene, preferably oxyethylene or oxypropylene, and more preferably oxyethylene. It should be noted that two or more oxyalkylene groups may be used in combination, in which case, each oxyalkylene group may be added randomly or in blocks.
[0089] m and n represent the average repeating number of the oxyalkylene group, and are 4 to 200, preferably 4 to 100, more preferably 4 to 50, further preferably 5 to 40, and particularly preferably 8 to 20.
[0090] In addition, R 3 , R 4 The alkyl group in can include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl and the like. 3 , R 4 Each independently represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom, and is preferably an alkyl group having 1 to 2 carbon atoms, more preferably a methyl group or a hydrogen atom, and further preferably a hydrogen atom.
[0091] Therefore, the functional group represented by formula (1-3) is particularly preferably -O-(CH2CH2O) m The functional group represented by -H, the functional group represented by formula (1-4) is particularly preferably -CH2O-(CH2CH2O) n -H. In addition, the suitable ranges of m and n in these cases are also as described above.
[0092] The polyvinyl acetal resin typically has an acetal group, a hydroxyl group, and an acetyl group. However, the polyvinyl acetal resin may be modified with a functional group or subjected to a re-acetylation reaction so as not to contain a hydroxyl group.
[0093] Furthermore, the polyvinyl acetal resin is preferably modified to have at least one functional group selected from the functional groups represented by the above formulae (1-1) to (1-4) as described above.
[0094] In the following, a polyvinyl acetal resin having any of the functional groups represented by the above formulae (1-1) to (1-4) may be described as a polyvinyl acetal resin (A) in order to distinguish it from other polyvinyl acetal resins.
[0095] In addition, the polyvinyl acetal resin having any of the functional groups represented by the above formula (1-1) and formula (1-2) may be described as a polyvinyl acetal resin (A-1) in order to distinguish it from other polyvinyl acetal resins.
[0096] Furthermore, the polyvinyl acetal resin having any of the functional groups represented by the above formula (1-3) and formula (1-4) may be described as a polyvinyl acetal resin (A-2) in order to distinguish it from other polyvinyl acetal resins.
[0097] The modification amount of the polyvinyl acetal resin (A) caused by the functional groups represented by formula (1-1) to formula (1-4) is, for example, 0.2 mol% to 25 mol%, preferably 0.3 mol% to 25 mol%. By making the modification amount within the above range, it is also easy to lower the glass transition temperature (Tg) and improve the adhesion of the intermediate film to organic glasses such as polycarbonate plates. The suitable value of the modification amount caused by the functional groups represented by the above formula (1-1) to formula (1-4) varies depending on the type of functional group.
[0098] The polyvinyl acetal resin (A-1) preferably has a modification amount of 5 mol% or more and 25 mol% or less caused by the functional groups represented by formula (1-1) and formula (1-2). By having a modification amount of 5 mol% or more, it is easy to lower the value of the polar component γsp and the glass transition temperature (Tg), and it is easy to improve the adhesion to highly hydrophobic resin materials such as polycarbonate. In addition, by being 25 mol% or less, it is easy to improve the adhesion by preventing the polar component γsp from becoming too low.
[0099] From these viewpoints, the modification amount caused by the functional groups represented by formula (1-1) and formula (1-2) is more preferably 6 mol% or more, further preferably 8 mol% or more, further preferably 10 mol% or more, and more preferably 22 mol% or less, further preferably 18 mol% or less.
[0100] In addition, for example, from the viewpoint of improving the above-mentioned adhesion, the amount of modification caused by the functional groups represented by formula (1-3) and formula (1-4) of the polyvinyl acetal resin (A-2) having any of the functional groups represented by formula (1-3) and formula (1-4) is preferably 0.2 mol% or more and 12 mol% or less. In addition, the amount of modification caused by the functional groups represented by formula (1-3) and formula (1-4) is more preferably 0.3 mol% or more, further preferably 0.4 mol% or more, further preferably 0.5 mol% or more, and further, more preferably 10 mol% or less, further preferably 8 mol% or less, and further preferably 6 mol% or less.
[0101] It should be noted that the amount of modification caused by each functional group represents the ratio of each functional group to all vinyl monomer units constituting the polyvinyl acetal resin, for example, the amount of modification caused by the functional groups shown in formula (1-1) and formula (1-2) represents the total ratio of these functional groups. It should be noted that the amount of modification can be measured by proton NMR on the polyvinyl acetal resin and calculated from the resulting spectrum. The acetalization degree, hydroxyl amount, and acetylation degree described later can also be measured by proton NMR and calculated from the resulting spectrum.
[0102] The polyvinyl acetal resin may not have the functional groups shown in the above formulas (1-1) to (1-4). Such a polyvinyl acetal resin may be a modified polyvinyl acetal resin having functional groups other than those shown in the formulas (1-1) to (1-4), or may be an unmodified polyvinyl acetal resin. Even if it is an unmodified polyvinyl acetal resin, the amount of hydroxyl groups may be reduced by reacetylation reaction as described later, thereby making it easy to lower the value of the polar component γsp and the glass transition temperature (Tg).
[0103] The polyvinyl acetal resin has a structural unit derived from vinyl as the main chain, and the functional groups represented by formulas (1-1) to (1-4) are preferably bonded to the structural unit derived from vinyl constituting the main chain. Therefore, the polyvinyl acetal resin preferably has any of the structural units represented by the following formulas (2-1) to (2-4), and more preferably has any of the structural units represented by the following formulas (2-1) and (2-2).
[0104]
[0105] (In formula (2-1) and (2-2), R 1 , R 2 The same as above. In formula (2-3) and (2-4), A 1 O.A 2 O, m, n, R 3 , and R 4 Same as above.)
[0106] The polyvinyl acetal resin typically has an acetal group, a hydroxyl group, and an acetyl group, that is, the polyvinyl acetal resin typically has structural units represented by the following formulas (3-1), (3-2), and (3-3). Therefore, the modified polyvinyl acetal resin preferably has structural units represented by the following formulas (3-1), (3-2), and (3-3), and at least one structural unit selected from the above formulas (2-1) to (2-4). Among them, the modified polyvinyl acetal resin more preferably has structural units represented by the following formulas (3-1), (3-2), and (3-3), and at least one structural unit selected from the above formulas (2-1) and (2-2).
[0107] However, in the case where the polyvinyl acetal resin is, for example, an unmodified polyvinyl acetal resin, it may not have a hydroxyl group as described above, and may not have a structural unit represented by formula (3-2). That is, the unmodified polyvinyl acetal resin may have structural units represented by the following formulas (3-1) and (3-3), and may further optionally have a structural unit represented by the following formula (3-2).
[0108] In addition, the polyvinyl acetal resin can be composed of structural units represented by the following formulas (3-1), (3-2) and (3-3), or structural units represented by the following formulas (3-1) and (3-3), and at least one structural unit selected from the above-mentioned formulas (2-1) to (2-4), but may also have structural units having functional groups other than these.
[0109]
[0110] (In formula (3-1), R 5 represents a hydrogen atom or a hydrocarbon group having 1 to 19 carbon atoms. )
[0111] The polyvinyl acetal resin is obtained by acetalizing polyvinyl alcohol or a modified polyvinyl alcohol obtained by modifying polyvinyl alcohol with an aldehyde as described above, and then modifying it as needed. However, as the polyvinyl alcohol, polyvinyl alcohol having a saponification degree of 80 to 99.8 mol% is generally used. In addition, in order to adjust the average degree of polymerization of the polyvinyl acetal resin to a desired range, the average degree of polymerization of the polyvinyl alcohol is preferably 300 or more and 5000 or less. The average degree of polymerization of the polyvinyl alcohol is obtained by the method according to JIS K6726 "Polyvinyl Alcohol Test Method (Polyvinyl Alcohol Test Method)".
[0112] The number of carbon atoms in the acetal group contained in the polyvinyl acetal resin is not particularly limited, and as shown in the above formula (3-1), it is, for example, 1 to 20, preferably 2 to 10, more preferably 2 to 6, and even more preferably 2, 3 or 4. Therefore, R shown in the above formula (3-1) 5 The number of carbon atoms in is preferably 1-9, more preferably 1-5, and further preferably 1-3.
[0113] As acetal group, specifically, butyral group is particularly preferred, therefore, as polyvinyl acetal resin, polyvinyl butyral resin is preferred. The acetalization degree (that is, acetal amount) of polyvinyl acetal resin is preferably 40 mol% or more and 85 mol% or less. In addition, the acetalization degree is more preferably 55 mol% or more, more preferably 60 mol% or more, in addition, more preferably 75 mol% or less, more preferably 70 mol% or less. By making the acetalization degree within these ranges, it is easy to make the amount of hydroxyl group be a moderate amount, while making it contain a certain amount of formula (1-1), formula (1-2), formula (1-3), and the functional group shown in formula (1-4).
[0114] The acetalization degree refers to the acetalization degree when the acetal group of the polyvinyl acetal-based resin is an acetoacetal group, and refers to the butyralization degree when the acetal group is a butyral group.
[0115] The degree of acetalization refers to the ratio of acetalized vinyl alcohol units to all vinyl monomer units constituting the polyvinyl acetal resin.
[0116] The hydroxyl amount of the polyvinyl acetal resin is preferably 35 mol% or less. If the hydroxyl amount is 35 mol% or less, the polar component γsp is prevented from becoming high, and the glass transition temperature (Tg) is also easily lowered. From the viewpoint of lowering the polar component γsp and the glass transition temperature (Tg) and making the adhesion to a highly hydrophobic resin material such as polycarbonate high, in the case of the polyvinyl acetal resin (A) (for example, resin (A-1) or resin (A-2)), the hydroxyl amount is more preferably 30 mol% or less, and further preferably 25 mol% or less.
[0117] The hydroxyl content of the polyvinyl acetal resin is preferably 0 mol% or more. However, in the case of the polyvinyl acetal resin (A) (for example, resin (A-1) or resin (A-2)), from the viewpoint of preventing the resin composition from becoming too soft, it is preferable that the hydroxyl content is a certain amount, for example, 5 mol% or more, preferably 9 mol% or more, more preferably 14 mol% or more, and further preferably 16 mol% or more.
[0118] In addition, in the case where the polyvinyl acetal resin is, for example, an unmodified polyvinyl acetal resin, the amount of hydroxyl groups needs to be low in order to prevent the polar component γsp from becoming high and to lower the glass transition temperature (Tg). Therefore, the amount of hydroxyl groups in the unmodified polyvinyl acetal resin is preferably 15 mol% or less, more preferably 10 mol% or less, further preferably 5 mol% or less, further preferably 3 mol% or less, and most preferably 0 mol%.
[0119] In addition, the hydroxyl group amount represents the ratio of the hydroxyl group to all the vinyl monomer units constituting the polyvinyl acetal-based resin.
[0120] The acetylation degree (acetyl group amount) of the above-mentioned polyvinyl acetal resin is, for example, 0.01 mol% or more and 50 mol% or less. However, in the case of the polyvinyl acetal resin (A) (for example, resin (A-1) or resin (A-2)), in order to make the modification amount caused by the functional groups represented by formula (1-1) to formula (1-4) be above a certain value, it is also better to make the acetylation degree below a certain value. Therefore, the acetylation degree of the polyvinyl acetal resin (A) (for example, resin (A-1) or resin (A-2)) is preferably 20 mol% or less, more preferably 15 mol% or less, further preferably 12 mol% or less, and further preferably 5 mol% or less.
[0121] The degree of acetylation of the polyvinyl acetal resin (A) (eg, resin (A-1) or resin (A-2)) is, as described above, for example, 0.01 mol % or more, preferably 0.1 mol % or more, and more preferably 0.5 mol % or more.
[0122] In addition, from the viewpoint of making the hydroxyl amount low and the polar component γsp high, and making the glass transition temperature (Tg) low, in the case of unmodified polyvinyl acetal resin, the acetylation degree is preferably above a certain value, preferably 15 mol% or more, more preferably 25 mol% or more, and further preferably 33 mol% or more. In addition, the acetylation degree of the unmodified polyvinyl acetal resin is as described above, for example, 50 mol% or less, preferably 45 mol% or less, and further preferably 42 mol% or less.
[0123] In addition, the acetylation degree shows the ratio of the acetyl group with respect to all the vinyl monomer units which comprise the polyvinyl acetal type resin.
[0124] The average degree of polymerization of the polyvinyl acetal resin is preferably 300 or more and 5000 or less. By adjusting the average degree of polymerization within the above range, mechanical strength, flexibility, etc. are well maintained, and adhesion is easily improved. From these viewpoints, the average degree of polymerization of the polyvinyl acetal resin is more preferably 500 or more, more preferably 700 or more, and more preferably 1500 or more. In addition, the average degree of polymerization is more preferably 4500 or less, more preferably 4000 or less, and more preferably 3500 or less.
[0125] The average degree of polymerization of the polyvinyl acetal-based resin is the same as the average degree of polymerization of the polyvinyl alcohol used as a raw material, and can be determined from the average degree of polymerization of the polyvinyl alcohol.
[0126] The aldehyde used in the production of polyvinyl acetal resin is not particularly limited, and is, for example, an aldehyde having 1 to 20 carbon atoms, but generally, an aldehyde having 2 to 10 carbon atoms is preferably used. The aldehyde having 2 to 10 carbon atoms is not particularly limited, and examples thereof include acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, 2-ethylbutyraldehyde, n-hexanal, n-octanal, n-nonanal, n-decanal, and benzaldehyde. Among them, aldehydes having 2 to 6 carbon atoms such as acetaldehyde, n-butyraldehyde, n-hexanal, and n-valeraldehyde are preferred, aldehydes having 2, 3, and 4 carbon atoms are more preferred, and n-butyraldehyde is further preferred. These aldehydes may be used alone or in combination of two or more.
[0127] The polyvinyl acetal-based resin used in the present invention may be used alone or in combination of two or more.
[0128] As long as the resin composition of the present invention exerts the effect of the present invention, it is possible to have a resin other than the polyvinyl acetal resin as a resin. As such a resin component, thermoplastic resins other than the polyvinyl acetal resin can be cited. However, it is good that the polyvinyl acetal resin is the main component. As thermoplastic resins other than the polyvinyl acetal resin, acrylic resins etc. can be cited.
[0129] Specifically, the total amount of the polyvinyl acetal resin is based on the total amount of resins contained in the resin composition, for example, 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, and most preferably 100% by mass. Therefore, the resin contained in the resin composition of the present invention can be composed only of polyvinyl acetal resin.
[0130] (Plasticizer)
[0131] The resin composition of the present invention may contain a plasticizer. The resin composition becomes soft by containing a plasticizer, and the glass transition temperature (Tg) of the resin composition can be low, so that the adhesion to various adherends such as resin materials such as organic glass and inorganic glass is high. However, the resin composition of the present invention does not contain a plasticizer, or even if it contains, it is preferably a small amount. By only containing or not containing a plasticizer in a small amount, the value of the polar component γsp of the surface free energy is prevented from becoming too high. In addition, even if the resin composition is used in long-term contact with a resin material with low polarity such as polycarbonate, the resin material can be prevented from being eroded by the plasticizer. Therefore, it is easy to ensure the transparency of the resin material, etc. even after long-term use. Further, the exudation of the plasticizer can also be suppressed.
[0132] Furthermore, the resin composition of the present invention can have good adhesion to resin materials such as polycarbonate by keeping the glass transition temperature (Tg) and the value of the polar component γsp of the surface free energy within the prescribed ranges even if the plasticizer is contained in a small amount or even if no plasticizer is contained.
[0133] The content of the plasticizer in the resin composition is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, further preferably 3 parts by mass or less, and further preferably 1 part by mass or less, relative to 100 parts by mass of the resin contained in the resin composition. The lower limit of the content of the plasticizer is 0 parts by mass.
[0134] The resin composition of the present invention, when using a polyvinyl acetal resin (A), that is, resin (A-1) or resin (A-2), most preferably does not contain a plasticizer, that is, the content of the plasticizer is 0 parts by mass. On the other hand, when the resin composition uses an unmodified polyvinyl acetal resin, it is preferable to contain a plasticizer from the viewpoint of lowering the glass transition temperature (Tg) of the resin composition and improving the adhesiveness.
[0135] As the plasticizer, for example, organic ester plasticizers, and phosphoric acid plasticizers such as organic phosphate plasticizers and organic phosphite plasticizers can be mentioned. One type of plasticizer can be used alone, or two or more types can be used in combination. Among them, organic ester plasticizers are preferred. As the organic ester plasticizer, monobasic organic acid esters and polybasic organic acid esters can be mentioned.
[0136] As the monobasic organic acid ester, esters of diols and monobasic organic acids can be mentioned. As the diol, polyalkylene glycols can be mentioned, wherein each alkylene unit has 2 to 4 carbon atoms, preferably 2 or 3 carbon atoms, and the number of repetitions of the alkylene units is 2 to 10, preferably 2 to 4. In addition, as the diol, monoalkylene glycols (i.e., the number of repetition units is 1) having 2 to 4 carbon atoms, preferably 2 or 3 carbon atoms can also be mentioned.
[0137] Specific examples of the diol include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, tetrapropylene glycol, and butylene glycol.
[0138] Examples of the monobasic organic acid include organic acids having 3 to 10 carbon atoms, and specific examples thereof include butyric acid, isobutyric acid, hexanoic acid, 2-ethylbutyric acid, heptanoic acid, n-octanoic acid, 2-ethylhexanoic acid, n-nonanoic acid, and decanoic acid.
[0139] Specific examples of the monobasic organic acid include triethylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylhexanoate, triethylene glycol dioctanoate, triethylene glycol di-n-octanoate, triethylene glycol di-n-heptanoate, tetraethylene glycol di-n-heptanoate, tetraethylene glycol di-2-ethylhexanoate, diethylene glycol di-2-ethylbutyrate, diethylene glycol di-2-ethylhexanoate, dipropylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylvalerate, tetraethylene glycol di-2-ethylbutyrate, diethylene glycol dicaprate, triethylene glycol di-n-heptanoate, tetraethylene glycol di-n-heptanoate, triethylene glycol di-2-ethylbutyrate, ethylene glycol di-2-ethylbutyrate, 1,2-propylene glycol di-2-ethylbutyrate, 1,3-propylene glycol di-2-ethylbutyrate, 1,4-butylene glycol di-2-ethylbutyrate, and 1,2-butylene glycol di-2-ethylbutyrate.
[0140] Examples of polybasic organic acid esters include ester compounds of dibasic organic acids having 4 to 12 carbon atoms, such as adipic acid, sebacic acid, and azelaic acid, and alcohols having 4 to 10 carbon atoms. The alcohols having 4 to 10 carbon atoms may have a linear, branched, or cyclic structure.
[0141] Specifically, dibutyl sebacate, dioctyl azelate, dihexyl adipate, dioctyl adipate, hexylcyclohexyl adipate, diisononyl adipate, heptylnonyl adipate, dibutyl carbitol adipate, mixed adipate, etc. can be mentioned. In addition, oil-modified sebacic acid alcohol acid, etc. can also be used. As mixed adipate, adipate made from two or more alcohols selected from alkyl alcohols having 4 to 9 carbon atoms and cyclic alcohols having 4 to 9 carbon atoms can be mentioned.
[0142] Examples of the organic phosphoric acid plasticizer include phosphoric acid esters such as tributoxyethyl phosphate, isodecylphenyl phosphate, and triisopropyl phosphate.
[0143] As the plasticizer, among the above, triethylene glycol di-2-ethylhexanoate (3GO) is particularly preferably used.
[0144] The resin composition may contain, in addition to the plasticizer, a known additive used in combination with the polyvinyl acetal resin. That is, the resin composition may be composed of a resin such as the polyvinyl acetal resin, but in addition to the resin, may contain a plasticizer mixed as needed, or an additive other than the plasticizer.
[0145] Specific examples of additives other than plasticizers include ultraviolet absorbers, infrared absorbers, antioxidants, light stabilizers, adhesion regulators, pigments, dyes, fluorescent brighteners, crystal nucleating agents, etc. The resin composition of the present invention may be diluted with a solvent and used in the form of a dilute solution.
[0146] [Method for producing polyvinyl acetal resin]
[0147] The polyvinyl acetal resin used in the resin composition of the present invention is obtained by acetalizing polyvinyl alcohol (also referred to as "raw polyvinyl alcohol") with an aldehyde, and then reacting it with a modifier as needed, or re-acetylation. The raw polyvinyl alcohol may be unmodified polyvinyl alcohol, but in the case of obtaining a modified polyvinyl acetal resin, a modified polyvinyl alcohol may be used as the raw polyvinyl alcohol.
[0148] Specifically, for example, when producing a polyvinyl acetal resin having at least one functional group selected from the functional groups represented by the above formula (1-1) and formula (1-2) (polyvinyl acetal resin (A-1)), it is preferably produced by the following production method (1).
[0149] (Manufacturing method (1))
[0150] In the present production method (1), the raw material polyvinyl alcohol is acetalized with aldehyde to obtain a polyvinyl alcohol acetal resin (hereinafter also referred to as raw material polyvinyl alcohol acetal resin). The raw material polyvinyl alcohol used here is obtained by saponifying polyvinyl ester, and is preferably unmodified polyvinyl alcohol.
[0151] Next, make R 1 or R 2 The modifying agent is reacted with the raw material polyvinyl acetal resin to introduce at least one of the functional groups represented by formula (1-1) and formula (1-2) into the raw material polyvinyl acetal resin. Here, the modifying agent is preferably a compound having a reactive group that reacts with the hydroxyl group of the raw material polyvinyl acetal resin to form a carbamate bond represented by formula (1-1) or an ester bond represented by formula (1-2).
[0152] Specifically, examples of the compound having the reactivity to react with a hydroxyl group to form a urethane bond include R 1 -NCO (where R 1 The isocyanate compound has high reactivity with the hydroxyl group of the raw material polyvinyl acetal resin, and the functional group represented by formula (1-1) can be easily introduced.
[0153] Examples of compounds having a reactive group that reacts with a hydroxyl group to form an ester bond include R 2 -COOH (where R 2 The same as above) is a carboxylic acid, or a carboxylic acid derivative such as anhydride, carboxylic acid ester, or carboxylic acid halide of the carboxylic acid. Among them, R 2 -COX (where R 2 As described above, X is a halogen atom. ) is preferably a carboxylic acid halide in which X is a chlorine atom. Carboxylic acid halides such as carboxylic acid chloride have high reactivity with the hydroxyl group of the raw material polyvinyl acetal resin, and the functional group represented by formula (1-2) can be easily introduced.
[0154] Specific examples of preferred isocyanate compounds include hexyl isocyanate, 2-ethylhexyl isocyanate, n-octyl isocyanate, n-nonyl isocyanate, n-decyl isocyanate, n-undecyl isocyanate, n-dodecyl isocyanate, n-tetradecyl isocyanate, n-hexadecyl isocyanate, n-octadecyl isocyanate, n-eicosyl isocyanate, and n-octadecyl isocyanate is preferred.
[0155] In addition, as preferred carboxylic acid chlorides, 2-ethylhexanoyl chloride, n-octanoyl chloride, n-nonanoyl chloride, n-decanoyl chloride, n-undecanoyl chloride, lauroyl chloride, myristoyl chloride, palmitoyl chloride, isopalmitoyl chloride, stearoyl chloride, isostearoyl chloride, oleoyl chloride, behenoyl chloride, etc. can be mentioned. Among them, any of 2-ethylhexanoyl chloride, lauroyl chloride, myristoyl chloride, palmitoyl chloride, and stearoyl chloride is preferred, and lauroyl chloride, myristoyl chloride, and palmitoyl chloride are more preferred.
[0156] In the above-mentioned production method (1), the reaction of the raw material polyvinyl acetal resin with the modifier such as isocyanate compound and carboxylic acid halide is not particularly limited. For example, the raw material polyvinyl acetal resin and the modifier are preferably heated to a solvent at a temperature of, for example, 30° C. to 150° C., preferably 50° C. to 140° C. The reaction can be carried out in the presence of a base or an acid. As the base, for example, pyridine is used.
[0157] However, the method for producing the polyvinyl acetal-based resin (A-1) is not limited to the above method, and the polyvinyl acetal-based resin (A-1) can also be produced by the following production method (2).
[0158] (Manufacturing method 2)
[0159] In the present manufacturing method (2), first, a modified polyvinyl alcohol is manufactured as a raw material polyvinyl alcohol. Specifically, a modifier is reacted with an unmodified polyvinyl alcohol obtained by saponifying a polyvinyl ester, and a functional group of formula (1-1) or formula (1-2) is introduced into a part of the side chain of the polyvinyl alcohol. It should be noted that the specific example of the modifier is as shown in the above-mentioned manufacturing method (1). Furthermore, the obtained modified polyvinyl alcohol is acetalized with an aldehyde to obtain a polyvinyl alcohol acetal resin (A-1).
[0160] For example, when producing a polyvinyl acetal resin (modified polyvinyl acetal resin (A-2)) having at least one of the functional groups represented by the above formula (1-3) and formula (1-4), it is preferably produced by the following production method (3).
[0161] (Manufacturing method (3))
[0162] In the present production method (3), first, polyoxyalkylene-modified polyvinyl alcohol is produced as a raw material polyvinyl alcohol. Specifically, a polymer is obtained by polymerizing a vinyl ester and a monomer containing a vinyl monomer having a polyoxyalkylene group, and then the polymer is saponified to obtain the polymer. Saponification generally uses an alkali or an acid, but preferably uses an alkali. As the PVA-based polymer, only one type may be used, or two or more types may be used in combination.
[0163] Next, the polyoxyalkylene-modified polyvinyl alcohol obtained above is preferably acetalized with aldehyde to obtain a modified polyvinyl alcohol acetal resin (A-2). The acetalization method is preferably carried out by a known method.
[0164] As the vinyl ester used in the production method (3), vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, branched alkane carboxylic acid vinyl esters, vinyl caproate, vinyl octanoate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, vinyl benzoate, etc. can be used. Among them, vinyl acetate is preferred.
[0165] Specific examples of the vinyl monomer having a polyoxyalkylene group used in the production method (3) include polyoxyalkylene vinyl ethers represented by the following formula (4-1) and polyoxyalkylene allyl ethers represented by the following formula (4-2).
[0166]
[0167] (In formula (4-1) and (4-2), A 1 O.A 2 O, m, n, R 3 , and R 4Same as above.)
[0168] Preferred specific examples of the vinyl monomer having a polyoxyalkylene group include polyoxyethylene monovinyl ether, polyoxyethylene polyoxypropylene monovinyl ether, polyoxypropylene monovinyl ether, polyoxyethylene monoallyl ether, polyoxyethylene polyoxypropylene monoallyl ether, and polyoxypropylene monoallyl ether. Among them, polyoxyethylene monovinyl ether, polyoxyethylene monoallyl ether, polyoxypropylene monovinyl ether, and polyoxypropylene monoallyl ether are more preferred.
[0169] In the case of an unmodified polyvinyl acetal resin, it is preferably produced by the following production method (4).
[0170] (Manufacturing method (4))
[0171] In the present manufacturing method (4), the raw material polyvinyl alcohol is acetalized with aldehyde to obtain a polyvinyl alcohol acetal resin (hereinafter also referred to as a raw material polyvinyl alcohol acetal resin). Here, as the raw material polyvinyl alcohol, an unmodified polyvinyl alcohol obtained by saponifying a polyvinyl ester is used. Next, the raw material polyvinyl alcohol acetal resin is subjected to a re-acetylation treatment to obtain an unmodified polyvinyl alcohol acetal resin. The re-acetylation treatment can be carried out by a conventionally known method, using acetic anhydride in the presence of a base such as pyridine. In addition, the re-acetylation treatment is preferably carried out by heating to, for example, a temperature of 50°C to 100°C, preferably 70°C to 90°C. By subjecting the polyvinyl alcohol acetal resin to a re-acetylation treatment, the amount of hydroxyl groups is reduced, and it is easy to lower the value of the polar component γsp of the surface free energy and the glass transition temperature (Tg).
[0172] [Method for producing resin composition]
[0173] The resin composition of the present invention can use the polyvinyl acetal resin manufactured as described above directly as a resin composition. In addition, the resin composition can be prepared by adding a plasticizer, an additive, etc. to the polyvinyl acetal resin manufactured as described above as needed. In addition, the resin composition can be diluted in a suitable solvent and used.
[0174] <Resin film>
[0175] The resin composition of the present invention can be used in any form, but is preferably used in a film form. That is, the present invention provides a resin film formed by the above-mentioned resin composition. It should be noted that the so-called resin film in this specification is widely referred to as a resin film not only in the case of a single resin film, but also in the case of being laminated, the film is equal to other components and becomes a layered or film-like form, and the material with a larger thickness generally referred to as a sheet is also referred to as a resin film. The thickness of the resin film is not particularly limited, but for example, it is more than 100 μm and less than 2000 μm, preferably more than 250 μm and less than 900 μm.
[0176] The resin film of the present invention can be composed of a single layer with the resin film formed by the above-mentioned resin composition as the first layer, or it can be composed of a multilayer film. The multilayer film only needs to have at least one layer of the above-mentioned resin film of the present invention as the first layer. For example, the multilayer film is a laminated body of the first layer formed by the above-mentioned resin composition of the present invention and a layer other than the first layer (hereinafter also referred to as "the second layer") formed by the resin composition of the present invention. It should be noted that the layer other than the first layer is preferably a resin layer containing a thermoplastic resin.
[0177] Furthermore, the multilayer film may be a laminate having two or more first layers formed from the resin composition of the present invention. In this case, the laminate may have a layer (second layer) formed from a composition other than the resin composition of the present invention.
[0178] The second layer has a composition and physical properties different from those of the first layer, and is preferably a resin layer containing a thermoplastic resin. Examples of the thermoplastic resin include polyvinyl acetal resins, acrylic resins, ethylene-vinyl acetate copolymer resins, ionomer resins, polyurethane resins, and thermoplastic elastomers. By using these resins, it is easy to ensure adhesion to the glass plate and the first layer. The thermoplastic resin may be used alone or in combination of two or more.
[0179] The second layer is preferably a layer formed of a resin composition composed of a thermoplastic resin, or a resin composition containing an appropriate plasticizer or an additive other than the plasticizer in addition to the thermoplastic resin.
[0180] The resin film of the present invention can be used in any application, but is preferably used in applications requiring transparency, light transmittance, etc. Specifically, it can be used as a transparent protective film used to protect optical components, a film for optical components constituting a part of an optical component, a glass resin film used for glass materials such as organic glass and inorganic glass, an adhesive film, an adhesive film, a dispersant for optical components, an adhesive for optical components, etc.
[0181] The resin film of the present invention is preferably used by being laminated so as to be in contact with a resin material such as polycarbonate or methacrylate, and more preferably used by being laminated so as to be in contact with a glass plate made of organic glass.
[0182] The resin composition of the present invention contains a polyvinyl acetal resin as described above, has a low glass transition temperature, and the value of the polar component γsp of the surface free energy is within a specified range. Therefore, if the resin film formed by the resin composition of the present invention is used in contact with a highly hydrophobic resin material such as polycarbonate, the adhesion to the resin material becomes good. In addition, since the resin material is also prevented from being eroded, the transparency can be improved.
[0183] The resin film of the present invention is preferably used as an intermediate film for laminated glass (hereinafter, sometimes referred to as "intermediate film"). The intermediate film is arranged between two laminated glass components and is used to bond the two laminated glass components. As described later, at least one of the two laminated glass components is preferably a glass plate made of organic glass such as a polycarbonate plate. The details of using the resin film in the intermediate film are described below.
[0184] [Method for producing resin film]
[0185] Resin film can be manufactured by molding resin composition into film by known method. Specifically, resin composition can be coated on support such as release sheet, or injected into mold frame, and appropriately heated, dried and molded into sheet as required, or molded by extrusion molding, compression molding, etc.
[0186] Furthermore, as described above, when a raw material polyvinyl acetal resin is reacted with a modifier to obtain a polyvinyl acetal resin, the polyvinyl acetal resin can be molded as follows. That is, a composition comprising a raw material polyvinyl acetal resin, a modifier, and other additives such as a plasticizer mixed as needed is applied on a support such as a release sheet, or injected into a mold frame, and then heated so that the modifier and the raw material polyvinyl acetal resin react and are molded into a film.
[0187] Furthermore, when the resin film has a multilayer structure, a resin composition for obtaining a layer (second layer) other than the first layer is also prepared, and the second layer is preferably obtained from the resin composition. In the case of a multilayer structure, the first layer and the second layer are appropriately overlapped to obtain an intermediate film, and the multilayer structure can be formed by coextrusion or the like.
[0188] <Interlayer film for laminated glass>
[0189] The interlayer film of the present invention comprises a first layer formed from the resin composition of the present invention as described above. Specifically, the interlayer film is Figure 1As shown in the figure, the intermediate film 30A may be composed of the first layer 31 formed by the above-mentioned resin composition alone. If the first layer 31 is composed alone, the two surfaces of the first layer 31 constitute the outermost surface in contact with a pair of laminated glass components (the first laminated glass component and the second laminated glass component 41, 42) constituting the laminated glass. Therefore, in the case where one or both of the first laminated glass component and the second laminated glass component 41, 42 are organic glass, the adhesion of the intermediate film 30A to the organic glass is improved, and at the same time, the corrosion of the organic glass by the intermediate film is effectively prevented, and the transparency of the laminated glass is also easily ensured. It should be noted that the organic glass is as described later, but is preferably a polycarbonate plate or a methacrylate plate, and is particularly preferably a polycarbonate plate.
[0190] In addition, the interlayer film may have a multilayer structure including at least a first layer formed of the above-mentioned resin composition. The interlayer film of the multilayer structure only needs to have at least one first layer. However, even in the case of a multilayer structure, the first layer preferably constitutes the outermost surface of the interlayer film. By constituting the outermost surface and arranging it at a position in contact with the laminated glass member as organic glass, the adhesion of the interlayer film to the organic glass can be improved, and at the same time, the corrosion of the organic glass by the interlayer film can be effectively prevented.
[0191] In addition, in the case of a multilayer structure, the first layer may have two or more layers. By having two or more layers, even in the case of a multilayer structure, the two outermost surfaces of the intermediate film may be constituted by the first layer. In the case of having two or more first layers, the composition of each layer may be different or the same.
[0192] The intermediate film may have a laminated structure including a first layer and a layer (second layer) other than the first layer. In this case, one of the outermost layers may be composed of the first layer and the other of the outermost layers may be composed of the second layer, or both outermost layers may be composed of the first layer.
[0193] When the intermediate film has a first layer and a second layer, for example Figure 2 As shown in FIG. 1 , the intermediate film 30B may be a two-layer structure of a first layer 31 and a second layer 32. Figure 3 As shown, the interlayer film 30C may be a three-layer structure in which the first layer 31A, the second layer 32, and the first layer 31B are provided in this order, or may be a structure of more than three layers. The details of the second layer are as described above.
[0194] When the outermost layer of the intermediate film is composed of the first layer and the outermost layer is composed of the second layer, it is preferred that the laminated glass member in contact with the outermost layer is composed of organic glass and the laminated glass member in contact with the outermost layer is composed of inorganic glass. Figure 2In the interlayer film 30B shown, it is preferred that the first laminated glass member 41 in contact with the first layer 31 is organic glass, and the second laminated glass member 42 in contact with the second layer 32 is inorganic glass.
[0195] Thus, the adhesion of the intermediate film to the organic glass can be increased, and the corrosion of the organic glass by the intermediate film can be effectively prevented. In addition, inorganic glass can also be bonded with high adhesion through the second layer, so that the intermediate film can bond with high adhesion to any laminated glass component.
[0196] Furthermore, when the interlayer film is a multilayer structure and the two outermost layers are composed of the first layer, it is preferred that the laminated glass component in contact with the outermost one is composed of organic glass, and the laminated glass component in contact with the other outermost layer is composed of either inorganic glass or organic glass. However, it is more preferred that the laminated glass components in contact with the two outermost layers are both composed of organic glass.
[0197] Therefore, for Figure 3 In the intermediate film 30C shown, the first interlayer glass member 41 in contact with one first layer 31A is preferably organic glass, and the second interlayer glass member 42 in contact with the other first layer 31B is organic glass or inorganic glass, but it is more preferable that both the first interlayer glass member and the second interlayer glass member 41, 42 are organic glass. With the above configuration, the adhesion of the intermediate film 30 to the organic glass can be increased, and the corrosion of the organic glass by the intermediate film can be effectively prevented.
[0198] However, the laminated glass member is not limited to organic glass or inorganic glass, and an organic film (resin film) may be used. The same configuration may be achieved by using an organic film instead of the organic glass.
[0199] (Adhesion strength of interlayer film)
[0200] In the present invention, it is preferred that the adhesive strength of a laminated glass sample obtained by pressing a pair of polycarbonate plate glasses according to JIS K6735 at 80° C. through the above-mentioned interlayer film is 100 N / 225 mm. 2 If the above bonding force is 100N / 225mm 2 The adhesiveness to organic glass such as polycarbonate plate is sufficiently high. From the viewpoint of ensuring a higher adhesive force, the above-mentioned adhesive force is more preferably 180N / 225mm. 2 Furthermore, if the adhesive strength during compression bonding at 80° C. is high as described above, sufficient adhesive strength can be ensured even during thermocompression bonding at a relatively low temperature, thereby improving the productivity of laminated glass.
[0201] It should be noted that the adhesive strength measurement method is performed on a laminated glass sample obtained by sequentially undergoing the following first, second, and third steps.
[0202] Step 1: Prepare an interlayer film of 15 mm in length and 15 mm in width, and prepare two polycarbonate glass plates of 2 mm in thickness, 25 mm in length and 100 mm in width in accordance with JIS K6735. The two polycarbonate glass plates are arranged so that their longitudinal directions are perpendicular to each other and overlapped in a cross shape via the interlayer film.
[0203] Step 2: To make the thickness of the interlayer film constant, a spacer having the same thickness as the interlayer film was used, and two polycarbonate glass plates superposed with the interlayer film interposed therebetween were temporarily pressed together in a vacuum laminator at 80° C. and 0.1 MPa for 3 minutes.
[0204] Step 3: The two polycarbonate glass plates that were temporarily pressed together were fully pressed together under conditions of 80° C. and 0.5 MPa for 1 hour.
[0205] Next, the obtained laminated glass samples were subjected to a cross peel test. Specifically, the maximum load (N) when one polycarbonate glass plate was peeled from another polycarbonate glass plate in a direction perpendicular to the bonding surface at a speed of 10 mm / min at 23°C was measured, and the maximum load (N) was defined as the adhesive force.
[0206] More specifically, as long as it is placed in Figure 4 The clamp shown in the figure can be used to measure the bonding force. The clamp is composed of a box body 11 and a pushing member 20. The box body 11 and the pushing member 20 are formed of SUS. The box body 11 is a rectangular parallelepiped with an open upper surface, and rectangular cutouts 14, 14 are set on the upper end faces of the side surfaces 13, 13 opposite to each other. The pushing member 20 is a U-shaped member provided with a rectangular base 16 and pushing pieces 17, 17 connected at right angles to the two end portions in the length direction of the base 16. The width W of each pushing piece 17 is 20mm, the thickness T is 5mm, and the distance L between the pushing pieces 17, 17 is 35mm.
[0207] The laminated glass sample 10 was arranged such that one polycarbonate plate glass 21 was placed between the cutouts 14 and 14 so that the other polycarbonate plate 22 was placed on the lower side. The maximum load (N) when the polycarbonate plate glass 31 was peeled off by applying a load in a straight downward direction X perpendicular to the bonding surface at a speed of 10 mm / min was measured, and the adhesive strength (N / 225 mm) was calculated from the maximum load (N). 2 ).
[0208] The interlayer film of the present invention has good adhesion to various organic glasses. Specifically, the adhesion of a laminated glass sample obtained by pressing a pair of methacrylate plate glasses at 100° C. through the interlayer film is preferably 80 N / 225 mm. 2 More than, more preferably 100N / 225mm 2 More than, more preferably 200N / 225mm 2 above.
[0209] Furthermore, the adhesive strength of the laminated glass sample obtained by pressing a pair of PET plate glasses at 80° C. through the interlayer film is preferably 80 N / 225 mm. 2 More than, more preferably 100N / 225mm 2 above.
[0210] The method for measuring the adhesive strength of the laminated glass sample obtained from acrylic plate glass and PET plate glass is the same as the method for measuring the adhesive strength of the laminated glass sample obtained from polycarbonate plate glass, except that the polycarbonate plate glass is replaced by acrylic plate glass or PET plate glass.
[0211] (Visible light transmittance)
[0212] Regarding the interlayer film of the present invention, when a laminated glass is produced using two polycarbonate plate glasses having a thickness of 2 mm and a visible light transmittance of 90% according to JIS K6735, the visible light transmittance of the laminated glass is preferably 70% or more. If the visible light transmittance is 70% or more, when a laminated glass is produced using the interlayer film of the present invention, the laminated glass can ensure high transparency. From such a viewpoint, the visible light transmittance is more preferably 80% or more, and further preferably 85% or more.
[0213] In addition, the visible light transmittance can be measured using a spectrophotometer in accordance with JIS R3211 (1998).
[0214] (Thickness of interlayer film)
[0215] The thickness of the interlayer film of the present invention is, for example, 100 μm to 2000 μm, preferably 250 μm to 900 μm. By setting the thickness of the interlayer film within such a range, the interlayer film will not be too thick and good adhesion to the laminated glass member can be achieved.
[0216] <Laminated glass>
[0217] The laminated glass of the present invention comprises a first laminated glass member, a second laminated glass member, and an intermediate film disposed between the first laminated glass member and the second laminated glass member. In the laminated glass, the first laminated glass member and the second laminated glass member are bonded via the intermediate film, the first laminated glass member is bonded to one outermost surface of the intermediate film, and the second laminated glass member is bonded to the other outermost surface of the intermediate film. The structure of the intermediate film is as described above.
[0218] The first laminated glass component and the second laminated glass component are each a glass plate, preferably selected from inorganic glass and organic glass. In addition, either one may be an organic film. In the laminated glass of the present invention, it is preferred that at least one laminated glass component is organic glass. In this case, as described above, the first glass component and the second glass component may be one organic glass and the other inorganic glass, or both organic glass. By using organic glass, the adhesion of the intermediate film to the laminated glass component can be improved, and the corrosion of the intermediate film to the laminated glass component can be effectively prevented.
[0219] The inorganic glass is not particularly limited, and examples thereof include various glass plates such as float glass, tempered glass, tinted glass, polished glass, patterned glass, wired glass, wired glass, ultraviolet absorbing plate glass, infrared reflecting plate glass, infrared absorbing plate glass, green glass, etc. The inorganic glass may be subjected to surface treatment, etc.
[0220] The thickness of the inorganic glass is not particularly limited, but is preferably 0.1 mm or more, more preferably 1.0 mm or more, and is preferably 5.0 mm or less, more preferably 3.2 mm or less.
[0221] Organic glass is not particularly limited, and various organic glass plates such as polycarbonate plates, methacrylate plates such as polymethyl methacrylate plates, polyester plates such as acrylonitrile styrene copolymer plates, acrylonitrile butadiene styrene copolymer plates, polyethylene terephthalate (PET) plates, fluorine resin plates, polyvinyl chloride plates, chlorinated polyvinyl chloride plates, polypropylene plates, polystyrene plates, polysulfone plates, epoxy resin plates, phenol resin plates, unsaturated polyester resin plates, and polyimide resin plates can be cited. Organic glass can also be appropriately surface treated.
[0222] Among the above, polycarbonate plates are preferred from the perspective of excellent transparency, impact resistance, and flame resistance, and methacrylate plates such as polymethyl methacrylate plates are preferred from the perspective of high transparency, weather resistance, and excellent mechanical strength, and polycarbonate plates are preferred among them. In the present invention, even if the interlayer film is used for highly hydrophobic organic glass such as polycarbonate plates and methacrylate plates as laminated glass components, it can be bonded to the laminated glass component with high adhesion. In addition, the organic glass can be prevented from being corroded by the interlayer film.
[0223] The thickness of the organic glass is not particularly limited, but is preferably 0.1 mm or more, more preferably 0.3 mm or more, and is preferably 5.0 mm or less, more preferably 3.0 mm or less.
[0224] The laminated glass of the present invention can be used in various fields, and specifically, is used as window glass in vehicles such as automobiles and trains, various transportation vehicles such as ships and airplanes, various buildings such as buildings, apartments, single-family houses, halls, and gymnasiums, and working machines such as cutting and grinding, and construction machines such as excavators and cranes.
[0225] [Method for manufacturing laminated glass]
[0226] The laminated glass can be manufactured by placing a pre-made intermediate film between the first laminated glass component and the second laminated glass component and performing thermal compression bonding. In the case where the intermediate film of the laminated glass of the present invention has a multi-layer structure, the multi-layer intermediate film can be pre-made and placed between the first laminated glass component and the second laminated glass component. In addition, between the first laminated glass component and the second laminated glass component, a plurality of resin films for forming the first layer, the second layer, etc. are overlapped, and the plurality of resin films are integrated to form the multi-layer intermediate film, and the first laminated glass component and the second laminated glass component are preferably bonded via the intermediate film.
[0227] The method of thermocompression bonding is not particularly limited, but in a state where an intermediate film or the like is arranged between a pair of glass components, it is better to apply pressure while heating them. The heating temperature is preferably above 60°C and below 150°C, more preferably above 70°C and below 140°C. In addition, the pressure is preferably above 0.4MPa and below 1.5MPa, more preferably above 0.5MPa and below 1.3MPa. It should be noted that the so-called pressure here is absolute pressure. In addition, the thermocompression bonding can include a method using an autoclave, a method using a hot press, etc., but it is preferably carried out using an autoclave.
[0228] In the manufacture of the above-mentioned laminated glass, after the intermediate film or a plurality of resin films are arranged between the first laminated glass member and the second laminated glass member, before the heat-pressing bonding, the air remaining between the pair of laminated glass members may be degassed as required. The degassed method is not particularly limited, but it is preferably performed by decompressing and sucking with a pressing roller or by placing in a rubber bag.
[0229] In addition, before hot press bonding, temporary bonding can be performed. The temporary bonding is preferably carried out, for example, by disposing an intermediate film or a plurality of resin films between a pair of laminated glass members and pressing them while heating as needed under a relatively low pressure. The temporary bonding is preferably carried out using a vacuum laminator, for example. When degassing is performed during the temporary bonding, it can be carried out after degassing or together with degassing.
[0230] Examples
[0231] The present invention will be described in more detail by way of examples, but the present invention is not limited by these examples in any way.
[0232] It should be noted that the measurement methods and evaluation methods of the physical property values in the present invention are as follows.
[0233] <Surface free energy>
[0234] Water and diiodomethane were taken into a syringe, and a 2 μL droplet was formed at the tip of the needle. The formed droplet was brought into contact with the resin films obtained in the respective examples and comparative examples, and droplets were formed on the resin films. It should be noted that the resin films were kept in the measurement environment for 24 hours before measurement. In addition, the formation of the droplets was carried out in an environment of a temperature of 23°C and a relative humidity of 50%. After 30 seconds of dropping, an image of the droplet was taken. By analyzing the image of the droplet, the contact angle was calculated by the θ / 2 method. The average value of 30 measurements was set as the contact angle. From the obtained contact angles of water and diiodomethane, the value of the polar component γsp of the surface free energy was calculated by the method described in the specification. It should be noted that as the measurement device, “DropMaster500” manufactured by Kyowa Interface Science Co., Ltd. was used.
[0235] <Glass transition temperature (Tg)>
[0236] The resin films obtained in the examples and comparative examples were cut out to a length of 10 mm and a width of 5 mm, and the viscoelasticity was measured using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., trade name “DVA-200”) under the following measurement conditions. The peak temperature of the loss tangent tanδ obtained from the results of the viscoelasticity measurement was read. In the temperature range of -50 to 150°C, the first peak temperature counted from the low temperature side was set as the glass transition temperature (Tg).
[0237] (Measurement conditions)
[0238] Deformation mode: shear mode, measurement temperature: -50°C to 200°C, heating rate: 5°C / minute, measurement frequency: 1 Hz, strain: 1%
[0239] <Modification amount, degree of acetalization, degree of acetylation, and hydroxyl amount>
[0240] The molar ratio of each unit can be determined by dissolving the polyvinyl acetal resin in chloroform-d and measuring it using 1H-NMR (nuclear magnetic resonance spectrum).
[0241] <PC Adhesion>
[0242] A resin film having a size of 15 mm in length and 15 mm in width was prepared, and two polycarbonate glass plates having a thickness of 2 mm, a length of 25 mm, and a width of 100 mm were prepared in accordance with JIS K6735. The two polycarbonate glass plates were arranged so that their longitudinal directions were perpendicular to each other and overlapped crosswise with the resin film interposed therebetween.
[0243] Then, in order to make the thickness of the resin film constant, a spacer having the same thickness as the resin film was used, and the two polycarbonate glass plates overlapped with the resin film were temporarily pressed for 3 minutes under the conditions of 80°C and 0.1 MPa in a vacuum laminator. Then, the temporarily pressed polycarbonate glass plates were further fully pressed for 1 hour under the conditions of 80°C and 0.5 MPa to obtain a laminated glass sample.
[0244] The obtained laminated glass samples were subjected to a cross peel test. Specifically, the maximum load (N) when the laminated glass samples were peeled at a speed of 10 mm / min in a direction perpendicular to the bonding surface at a temperature of 23°C was measured, and the maximum load (N) was defined as the adhesive force, and the test was evaluated based on the following criteria.
[0245] (Evaluation Criteria)
[0246] AA: Maximum load is above 180N.
[0247] A: The maximum load is 100N or more and less than 180N.
[0248] A - : The maximum load is greater than 80N and less than 100N.
[0249] B: Maximum load is less than 80N.
[0250] <PC Corrosion>
[0251] A resin film having a size of 25 mm in length and 50 mm in width was prepared, and two polycarbonate glass plates having a thickness of 2 mm, a length of 25 mm, and a width of 50 mm were further prepared in accordance with JIS K6735. The polycarbonate glass plates were heated at 80° C. overnight (24 hours) to dry the moisture contained in the polycarbonate glass plates. Next, the two polycarbonate glass plates were overlapped via the resin film.
[0252] The laminated polycarbonate glass plates were then temporarily pressed at 80°C and 0.1 MPa for 3 minutes, and then fully pressed at 80°C and 0.5 MPa for 1 hour to obtain a laminated glass sample.
[0253] The total light transmittance of the obtained laminated glass sample measured using a spectrophotometer ("U-4100" manufactured by Hitachi HiTech) in accordance with JIS R3211 (1998) is set as x1. Next, the laminated glass sample is placed in a constant temperature bath at 100°C and heated for 10 days (240 hours). The heated laminated glass sample is returned to room temperature (23°C), and the total light transmittance is measured using a spectrophotometer in the same manner, and is set as x2.
[0254] (Evaluation Criteria)
[0255] A: The total light transmittance is 85% or more.
[0256] B: The total light transmittance is less than 85%.
[0257] <Adhesion (to acrylic)>
[0258] In the same manner, two methacrylate plate glasses were placed with a resin film interposed therebetween to produce a laminated glass sample, and the maximum load (N) was measured by the same method. The maximum load (N) was defined as the adhesive strength, and the evaluation was performed based on the above-mentioned evaluation criteria, except that the methacrylate plate glass of Comoglas (code: CGP) manufactured by Kuraray Co., Ltd. was used instead of the polycarbonate plate glass, and the temperature during the pressing (temporary pressing and final bonding) was changed from 80°C to 100°C.
[0259] <Adhesion (to PET)>
[0260] The same operation was performed except that PET plate glass PET-6010 (No. 6010) manufactured by Techron Glass was used instead of polycarbonate plate glass, and two PET plate glasses were placed through a resin film to prepare a laminated glass sample, and the maximum load (N) was measured by the same method. The maximum load (N) was set as the adhesive force, and the evaluation was performed based on the above evaluation criteria.
[0261] (Example 1)
[0262] In a 500 mL detachable flask dried under a nitrogen stream, 300 g of THF and 30 g of polyvinyl butyral (average degree of polymerization 1700, acetylation degree 1 mol%, hydroxyl content 33 mol%, acetalization degree 66 mol%, unmodified polyvinyl butyral, PVB1) were added, and the polyvinyl butyral was dissolved while stirring at 65°C.
[0263] 30 g of octadecyl isocyanate as a modifier was added to the solution and stirred for 10 minutes. The solution was taken out from a detachable flask, injected into an aluminum pad laid with the peeling-treated surface of a PET release film (trade name "PET50D1-C", manufactured by NIPPA) as the upper surface, and then heated in an oven at 130°C for 2 hours to react, thereby obtaining a film formed by a polyvinyl acetal resin having a functional group of formula (1-1). The obtained polyvinyl acetal resin was press-formed at a temperature of 160°C and a pressure of 20 MPa to obtain a resin film with a thickness of 800 μm. The obtained resin film was measured using an infrared spectrophotometer (IR), and the result showed that the isocyanate group (wave number 2260 cm -1 ) disappeared, thus confirming the progress of the reaction.
[0264] (Example 2)
[0265] The same procedure as in Example 1 was carried out except that PVB2 (average degree of polymerization 830, acetylation degree 2 mol%, hydroxyl content 33 mol%, acetalization degree 65 mol%, unmodified polyvinyl butyral) was used as the raw material instead of PVB1.
[0266] (Example 3)
[0267] In a 500 mL detachable flask dried under a nitrogen stream, 300 g of THF and 30 g of PVB2 as a raw material of polyvinyl butyral were added, and the polyvinyl butyral was dissolved while stirring at 65°C. 15.9 g of pyridine and 22.0 g of lauroyl chloride were added to the solution, and the reaction was carried out at 65°C for 3 hours. Then, the reaction solution was recovered, washed three times with a mixed solvent of water and methanol (mass ratio 1:1) and then dried to obtain a polyvinyl acetal resin having a functional group of formula (1-2). The obtained polyvinyl acetal resin was press-molded at a temperature of 160°C and a pressure of 20 MPa to obtain a resin film.
[0268] (Example 4)
[0269] The same procedure as in Example 3 was carried out except that the amount of pyridine added was changed to 11.3 g and 11.7 g of 2-ethylhexanoyl chloride was used instead of 22.0 g of lauroyl chloride.
[0270] (Example 5)
[0271] The same procedure as in Example 3 was carried out except that the amount of pyridine added was changed to 15.9 g and 16.3 g of 2-ethylhexanoyl chloride was used instead of 22.0 g of lauroyl chloride.
[0272] (Example 6)
[0273] The same procedure as in Example 3 was carried out except that the amount of pyridine added was changed to 15.9 g and 27.6 g of palmitoyl chloride was used instead of 22.0 g of lauroyl chloride.
[0274] (Example 7)
[0275] In a 500 mL detachable flask dried under a nitrogen stream, 300 g of pyridine and 30 g of raw material polyvinyl butyral (acetalization degree 62 mol%, hydroxyl amount 30 mol%, acetyl group 8 mol%, polymerization degree 3200, unmodified polyvinyl acetal, PVB3) were added, and the raw material polyvinyl butyral was dissolved while stirring with a stirring blade. Then, 45.6 molar equivalents of acetic anhydride were added and stirred at 80°C for 4 hours. After removing pyridine under reduced pressure, the reactant was washed with water 3 times and dried to obtain a polyvinyl butyral resin (acetalization degree 62 mol%, acetyl group 38 mol%, polymerization degree 3200, unmodified polyvinyl acetal).
[0276] 100 parts by mass of the obtained dried product and 10 parts by mass of a plasticizer (triethylene glycol di-2-ethylhexanoate, 3GO) were fully kneaded to obtain a resin composition, which was press-molded to obtain a resin film (intermediate film) having a thickness of 800 μm.
[0277] (Example 8)
[0278] [Synthesis of Ethylene Oxide Modified Polyvinyl Alcohol]
[0279] In a flask equipped with a stirrer, a thermometer, a dropping funnel and a reflux cooler, 1000 parts by mass of vinyl acetate, 320 parts by mass of polyoxyethylene monovinyl ether having an average repeating unit m=10, and 300 parts by mass of methanol were added, and after nitrogen substitution in the system, the temperature was raised to 60°C. 1.1 parts by mass of 2,2-azobisisobutyronitrile was added to the system, and polymerization was started. The polymerization was stopped 5 hours after the start of the polymerization. The solid content concentration in the system at the time of the polymerization stop was 53% by mass, and the polymerization yield relative to all monomers was 65% by mass. After removing the unreacted monomers under reduced pressure, a 40% by mass methanol solution of the copolymer was obtained. The obtained copolymer contained 96.0 mol% of vinyl acetate units and 4.0 mol% of alkyl vinyl ether units containing ethylene oxide, which was confirmed by quantitative analysis of the unreacted monomers.
[0280] 100 parts by mass of the methanol solution of the obtained copolymer was stirred at 40°C, and 2.0 parts by mass of a 3% by mass NaOH methanol solution was added, and the mixture was fully mixed and allowed to stand. After 2 hours, the solidified polymer was crushed with a crusher, washed with methanol, and dried to obtain a polymer powder (ethylene oxide-modified polyvinyl alcohol). The degree of saponification of the ethylene oxide-modified polyvinyl alcohol was 90.1 mol%, the amount of ethylene oxide units was 4.0 mol%, and the degree of polymerization was 700.
[0281] [Preparation of polyvinyl butyral (PVB5)]
[0282] 280 g of the obtained polymer powder was added to 2100 g of pure water and stirred at 90° C. for about 2 hours to dissolve it. The solution was cooled to 40° C., 135 parts by mass of hydrochloric acid with a concentration of 35% by mass and 130 parts by mass of n-butylaldehyde were added, the liquid temperature was lowered to 20° C., and the temperature was maintained to carry out acetalization reaction to precipitate the reaction product. Then, the liquid temperature was maintained at 40° C. for 3 hours to complete the reaction, and a white powder of polyvinyl acetal resin (PVB5) was obtained by neutralization, water washing and drying by conventional methods.
[0283] [Production of resin film]
[0284] The obtained polyvinyl acetal-based resin (PVB5) was press-molded in the same manner as in Example 1 to obtain a resin film (intermediate film) having a thickness of 800 μm.
[0285] (Example 9)
[0286] The amount of 3 mass % NaOH methanol solution during the synthesis of ethylene oxide-modified polyvinyl alcohol was changed to 6.2 mass parts, and ethylene oxide-modified polyvinyl alcohol having a polymerization degree of 690 was obtained. In addition, the amount of 35 mass % hydrochloric acid during the preparation of polyvinyl butyral was changed to 160 mass parts, and the amount of n-butyraldehyde was changed to 150 mass parts, and a resin film (intermediate film) was produced by the same method as in Example 8. It should be noted that the polyvinyl acetal resin produced in Example 9 was PVB6.
[0287] (Comparative Example 1)
[0288] 100 parts by mass of PVB1 (average degree of polymerization 1700, acetylation degree 1 mol%, hydroxyl content 33 mol%, acetalization degree 66 mol%, unmodified polyvinyl butyral) and 40 parts by mass of a plasticizer (3GO) were mixed to obtain a resin composition, and the obtained resin composition was press-molded by the same method as in Example 1 to obtain a resin film.
[0289] (Comparative Example 2)
[0290] A resin film was produced in the same manner as in Comparative Example 1 except that the blending amount of the plasticizer (3GO) was changed to 20 parts by mass.
[0291] (Comparative Example 3)
[0292] A resin film was produced in the same manner as in Example 7 except that the plasticizer (3GO) was not added.
[0293] (Comparative Example 4)
[0294] PVB4 (average degree of polymerization 490, acetylation degree 2 mol%, hydroxyl amount 21 mol%, acetalization degree 77 mol%, unmodified polyvinyl butyral) was press-molded in the same manner as in Example 1 to obtain a resin film.
[0295] (Comparative Example 5)
[0296] The same procedure as in Example 3 was carried out except that the amount of pyridine added was changed to 4.5 g and 4.7 g of 2-ethylhexanoyl chloride was used instead of 22.0 g of lauroyl chloride.
[0297] [Table 1]
[0298]
[0299] ※The abbreviations in Table 1 are as follows.
[0300] C18 isocyanate: n-octadecyl isocyanate
[0301] C12 Chloride: Lauroyl Chloride
[0302] Branched C8 chloride: 2-ethylhexanoyl chloride
[0303] C16 Chloride: Palmitoyl Chloride
[0304] ※The amount of the modifier compounded is the amount of the modifier compounded per 100 parts by mass of the raw material polyvinyl acetal.
[0305] * The modification amount, acetalization degree, acetylation degree, and hydroxyl group amount in Table 1 are values related to the polyvinyl acetal-based resin contained in the obtained resin film (resin composition).
[0306] ※The content of the plasticizer is based on 100 parts by mass of the resin (polyvinyl acetal resin).
[0307] In the above embodiments, the resin composition contains a polyvinyl acetal resin, the glass transition temperature is 50° C. or less, and the polar component γsp is 0.1 mJ / m 2 Above and 8.0mJ / m 2The value below 0.05 is sufficient to prevent the corrosion of the polycarbonate plate by the resin composition even after long-term heating, and the adhesion to the polycarbonate plate becomes good.
[0308] On the other hand, in each of the comparative examples, the glass transition temperature exceeded 50°C, or the polar component γsp exceeded 8.0 mJ / m 2 Therefore, it is impossible to prevent the corrosion of the polycarbonate plate caused by the resin composition and at the same time make the adhesion to the polycarbonate plate good.
[0309] Explanation of symbols
[0310] 30A, 30B, 30C Interlayer film for laminated glass
[0311] 31, 31A, 31B 1st floor
[0312] 32 Layer 2
[0313] 41 No. 1 Laminated Glass Component
[0314] 42 Second laminated glass component.
Claims
1. A resin composition comprising a polyvinyl acetal resin, having a glass transition temperature of 50° C. or less and a polar component γsp of surface free energy obtained by a Kaelble-Uy method of 0.1 mJ / m 2 Above and 8.0mJ / m 2 The following values, The polyvinyl acetal resin has at least one functional group selected from the group consisting of the following formula (1-1), formula (1-2), formula (1-3), and formula (1-4), In formula (1-1) and (1-2), R 1 , R 2 Each independently is a hydrocarbon having 2 to 30 carbon atoms; in formula (1-3) and (1-4), A 1 O.A 2 O is independently an oxyalkylene group having 2 to 4 carbon atoms, m and n are average repeating numbers, which are 4 to 200; R 3 , R 4 Each independently represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom; it should be noted that in formula (1-3) and formula (1-4), the oxyalkylene group may be a single species or a mixture of two or more species. The resin composition does not contain a plasticizer, or contains a plasticizer in an amount of 10 parts by mass or less based on 100 parts by mass of the resin contained in the resin composition.
2. The resin composition according to claim 1, wherein the polyvinyl acetal resin has structural units represented by formula (3-1), formula (3-2) and formula (3-3), and at least one structural unit selected from formula (2-1) to formula (2-4), In formula (3-1), R 5 represents a hydrogen atom or a hydrocarbon group having 1 to 19 carbon atoms, In formula (2-1) and (2-2), R 1 , R 2 are each independently a hydrocarbon group having 2 to 30 carbon atoms. In formulas (2-3) and (2-4), A 1 O.A 2 O is independently an oxyalkylene group having 2 to 4 carbon atoms, m and n are average repeating numbers of 4 to 200, and R 3 , R 4 Each independently represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. In formula (2-3) and formula (2-4), the oxyalkylene group may be a single type or a mixture of two or more types.
3. The resin composition according to claim 1 or 2, wherein R 1 , R 2 Each is independently an alkyl group having 2 to 30 carbon atoms.
4. The resin composition according to claim 3, wherein R 1 , R 2 Each is independently an alkyl group having 8 to 18 carbon atoms. 5 . The resin composition according to claim 1 , wherein in the polyvinyl acetal resin, the modification amount caused by the functional groups represented by formula (1-1) and formula (1-2) is 5 mol % or more and 25 mol % or less. 6 . The resin composition according to claim 5 , wherein in the polyvinyl acetal resin, the modification amount caused by the functional groups represented by formula (1-1) and formula (1-2) is 6 mol % or more and 22 mol % or less. 7 . The resin composition according to claim 1 , wherein in the polyvinyl acetal resin, the modification amount caused by the functional groups represented by formula (1-3) and formula (1-4) is 0.2 mol % or more and 12 mol % or less. 8 . The resin composition according to claim 7 , wherein in the polyvinyl acetal resin, the modification amount caused by the functional groups represented by formula (1-3) and formula (1-4) is 0.5 mol % or more and 6 mol % or less.
9. The resin composition according to claim 1, wherein the polar component γsp of the surface free energy obtained by the Kaelble-Uy method is 0.3 mJ / m 2 Above and 6.0mJ / m 2 the following. 10 . An interlayer film for laminated glass, comprising a first layer made of the resin composition according to claim 1 . 11 . The interlayer film for laminated glass according to claim 10 , wherein the interlayer film for laminated glass is composed of the first layer. 12 . The interlayer film for laminated glass according to claim 10 , wherein the thickness of the interlayer film for laminated glass is 100 μm or more and 2000 μm or less. 13 . A laminated glass comprising the interlayer film for laminated glass according to claim 10 , and a first laminated glass member and a second laminated glass member, wherein the interlayer film for laminated glass is arranged between the first laminated glass member and the second laminated glass member. 14 . The laminated glass according to claim 13 , wherein at least one of the first laminated glass member and the second laminated glass member is a polycarbonate plate or a methacrylate plate.
